(untitled) (Journal of Pharma Insights and Research, 2025)
Nanoemulsions are thermodynamically stable colloidal dispersions with droplet sizes ranging from 20 to 200 nm. These systems improve drug solubility, stability, and bioavailability through their unique physicochemical properties and versatile delivery capabilities. The formulation of nanoemulsions involves careful selection of oils, surfactants, and preparation methods - either high-energy mechanical processes or low-energy spontaneous emulsification techniques. The resulting nanoscale droplets exhibit remarkable stability and can be tailored for various administration routes including oral, parenteral, topical, and ocular delivery. Recent developments show their potential in improving the pharmacokinetic profiles of poorly water-soluble drugs, enabling targeted delivery, and reducing dosing frequency. Nanoemulsions are also used in food technology, cosmetics, and agriculture. Nanoemulsions improves the therapeutic efficacy of anti-cancer drugs, improving ocular drug delivery, and facilitating brain targeting through intranasal administration. Their ability to protect sensitive bioactive compounds while maintaining optimal droplet size distribution makes them particularly valuable for commercial pharmaceutical formulations. Despite these advantages, considerations regarding preparation methods, stability optimization, and regulatory compliance remain crucial for successful implementation in clinical applications.